Filling the Gaps: Impacts of farmers group learning process on empowerment and gender equality in Sulawesi, Indonesia - Mulyoutami, Elok (World Agroforestry Centre, 2017)
Presented by Elok Mulyoutami (WAC), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.